2010
DOI: 10.1177/0022034510388034
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Signaling in Human Oral Keratinocytes and Wound Repair

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. ABSTRACT Catecholamines are present in saliva, but their influence on oral epithelium is not understood. Because psychological stress increases salivary catecholamines and impairs oral mucosal wound healing, we sought to determine if epithelial adrenergic signaling could link these two findings. We found that cultured human oral keratinocytes (HOK) express the α 2B -and β 2 -adrenergic receptors (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
1
32
0
6
Order By: Relevance
“…Sivamani et al [26] have shown that the catecholamines released in the wound site decrease the keratinocyte migration mediated by ARs. It has also been described that the activation of β 2 -ARs leads to the in vitro and in vivo inhibition of keratinocytes migration [31, 32], and promotes the recruitment of polymorphonuclear cells by delaying the wound-healing process mediated by the increased IL-6 levels [33]. Furthermore, Shome et al [34] suggested that the neurotransmitter dopamine inhibits the VEGF-induced migration of murine mesenchymal progenitor cells to the wound site in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Sivamani et al [26] have shown that the catecholamines released in the wound site decrease the keratinocyte migration mediated by ARs. It has also been described that the activation of β 2 -ARs leads to the in vitro and in vivo inhibition of keratinocytes migration [31, 32], and promotes the recruitment of polymorphonuclear cells by delaying the wound-healing process mediated by the increased IL-6 levels [33]. Furthermore, Shome et al [34] suggested that the neurotransmitter dopamine inhibits the VEGF-induced migration of murine mesenchymal progenitor cells to the wound site in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,11,12 Local cortisol and epinephrine synthesis impairs keratinocyte migration and ultimately delays epithelization. 3,5 HEKs and epidermis in vitro and ex vivo, along with porcine epidermis in vivo, express CYP11B1, an enzyme necessary for the cortisol production, and produce clinically relevant levels of cortisol.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…Activation of b2AR decreases human keratinocyte migratory speed, delays healing of an in vitro scratch wound assay, impairs healing of an excisional human skin wound ex vivo, delays healing of acute surgical wounds in vivo, and results in impairment of oral mucosal wound healing. 5,[13][14][15][16][17] Similar to CYP11B1, the epidermal level of the epinephrine synthesizing enzyme PNMT is up-regulated during burn wound injury. Burn wounding of skin induces local epidermal generation of epinephrine by up-regulation of the enzyme, PNMT, required for epinephrine synthesis in the peri-wound epidermis.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations